Perbedaan Tingkat Pengetahuan Penulisan Resep Pada Mahasiswa Tingkat Awal Dan Tingkat Akhir Tahap Sarjana Program Studi Kedokteran Universitas Malahayati - Sri Maria; Tussy Triwahyuni; Hetty Rusmini; Dicky Tama Jaya Pasa (Universitas Malahayati, 2022)
ABSTRACT Prescription writing is one of the materials studied by medical students, especially final year students because they have passed almost all clinical blocks. Based on the results of research that has been carried out regarding the level of prescribing knowledge in early-stage undergraduate students of the Malahayati University General Medicine Study Program, Class of 2019, it shows that most of the respondents who have good prescribing knowledge are 108 people (77.7%). Meanwhile, in research that has been conducted on final year undergraduate students of the Malahayati University medical study program Force in 2017, data obtained from 190 respondents who filled out the prescribing knowledge level questionnaire obtained (48.4%) good knowledge. To find out the difference in the level of knowledge of prescription writing in students in the early and final stages of the undergraduate medical study program at the University. The type of research used in this research is quantitative analysis. By using secondary data from previous research. Of 226 respondents consisting of 74 men and 152 women who filled out the questionnaire on the level of knowledge of prescription writing, the majority of the initial level 62 respondents (54.9%) had sufficient knowledge, while at the final level the majority had good knowledge 57 respondents (50.4%). The results of the analysis obtained a p-value of 0.000 in this case p-value of 0.05 which means there is a significant difference in the level of knowledge of prescription writing in early and final year students. There is a difference in the level of knowledge of prescription writing in students in the early and final stages of the Medical Study Program of Malahayati University in 2021. Keywords: Knowledge Level, Prescription Writing, Student ABSTRAK Penulisan resep merupakan salah satu materi yang di pelajari mahasiswa kedokteran, terutama mahasiswa tingkat akhir karena telah melewati hampir seluruh blok klinis. Berdasarkan hasil penelitian yang telah dilakukan mengenai tingkat pengetahuan penulisan resep pada mahasiswa tingkat awal tahap sarjana Program Studi Kedokteran Umum Universitas Malahayati Angkatan Tahun 2019, menunjukan bahwa sebagian besar reponden yang memiliki pengetahuan penulisan resep yang baik sebanyak 108 orang (77,7%). Sedangkan pada penelitian yang telah dilakukan pada mahasiswa tingkat akhir tahap sarjana program studi kedokteran Universitas Malahayati Angkatan tahun 2017, data yang diperoleh dari 190 responden yang mengisi kuesioner tingkat pengetahuan penulisan resep didapatkan (48.4%) pengetahuan baik. Tujuan penelitian untuk mengetahui perbedaan tingkat pengetahuan penulisan resep. Jenis penelitian yang digunakan dalam penelitian ini adalah analitik kuantitatif. Dengan menggunakan data sekunder dari penelitian sebelumnya. Dari 226 responden yang terdiri dari 74 laki-laki dan 152 perempuan yang mengisi kuesioner tingkat pengetahuan penulisan resep didapatkan mayoritas tingkat awal 62 responden (54,9%) pengetahuan cukup, sedangkan pada tingkat akhir mayoritas berpengetahuan baik 57 responden (50,4%). Hasil analisis diperoleh nilai p value 0,000 dalam hal ini p value ≤ 0,05 yang berarti ada perbedaan bermakna pada tingkat pengetahuan penulisan resep pada mahasiswa tingkat awal dan tingkat akhir. Terdapat Perbedaan Tingkat Pengetahuan Penulisan Resep Pada Mahasiswa Tingkat Awal Dan Tingkat Akhir Tahap Sarjana Program Studi Kedokteran Universitas Malahayati Tahun 2020. Kata Kunci: Tingkat Pengetahuan, Penulisan Resep, Mahasiswa